Synergistic mechanisms in co-pyrolysis of lignin and polystyrene: A comprehensive study integrating experiments, ReaxFF-MD simulations, and kinetics - Fang Xu; Mingjun Liu; Wenxiao Wang; Mohan Zhao; Rui Zhang; Shuang Wu; Shuo Pan; Jingru Bai; Qing Wang (Biomass and Bioenergy, 2027)

Insights into liquid phase sintering mechanism of high-alumina and low-silica hematite ores - Wanlong Fan; Zhiwei Peng; Tuo Pan; Huibo Liu; Shaochang Nie; Lin Xiong; Qiang Zhong; Mingjun Rao (Minerals Engineering, 2026)

Mechanistic characterization of the discrepancies in enrichment of nitrate between agricultural and urban-industrial rivers in the semi-arid areas of northern China: Insights from multi-element stable isotope analysis - Ang Dong; Yu Liu; Guiqi Liu; Guangzhi Rong; Shuaihao Liu; Mingjun Mo; Haixia Wang; Guoguang Wang (Journal of Hydrology, 2026)

Westerly-associated inverse altitude effects in near-surface water vapor isotopes across Central Asian mountain–basin systems - Yudong Shi; Shengjie Wang; Kun Liu; Haixiang Jie; Shijun Lei; Mingjun Zhang (Global and Planetary Change, 2026)

PotatoScope: Morphology–Aware Compact Detection for Potato Foliar Disease Recognition - Mingjun Liu (Potato Research, 2026)

RBM10 suppresses porcine epidemic diarrhea virus replication by degrading nonstructural protein 3 through selective autophagy - Mingyu Liu; Zhenpeng Tang; Huixin Zhu; Jinxiu Lou; Yangyang Zhang; Mingjun Ye; Yufan Xu; Juan Bai; Ping Jiang; Zhen Yang; Gongguan Liu; Xianwei Wang (Veterinary Microbiology, 2026)

Decoupling of evapotranspiration from atmospheric demand: mechanistic insights into the local evaporation paradox in arid shrublands via physical and physiological resistance thresholds - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Shengjie Wang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Zhilan Wang; Meilin Sun; Peng Zhao; Shiquan Liu (Journal of Hydrology, 2026)

Activation of periodate driven by the synergistic interaction between inherent soil Fe and organic matter for adiazine degradation: Mechanisms, soil-type effects, and soil property changes - Yue Zhang; Caixia Yan; Yabing Chen; Yuyan Liu; Mingjun Ding; Peng Wang; Haofeng Liu; Minghua Nie (Journal of Hazardous Materials, 2026)

Structural and operational optimization of cold storage system for enhanced energy efficiency, rapid cold release and economic benefits - Yuan Lv; Zhimei Zuo; Zizhuang Ma; Wang Cheng; Fan Wang; Chuanxiao Cheng; Zheng Ling; Lanlan Jiang; Tao Yu; Mingjun Yang; Lei Yang; Yu Liu; et al. (Journal of Cleaner Production, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Experimental study on the dynamic characteristics of sandstone-mudstone mixed rockfill based on large-scale cyclic triaxial tests - Jianqing Jiang; Dongyi Ya; Mingjun Tian; Youneng Liu; Guijiang Huang; Sizhou Yan; Jinqiang Zhang (Bulletin of Engineering Geology and the Environment, 2026)

A fuel modification strategy for cleaner iron ore sintering: lime milk-derived calcium oxide coating of coke breeze for combustion regulation and multi-pollutant reduction - Wenzheng Jiang; Qiang Zhong; Fuliang Teng; Jie Liu; Zishuo Gao; Hongyun Yin; Liang Fan; Bin Xu; Mingjun Rao; Zhiwei Peng (Journal of Cleaner Production, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

In situ conversion of KNiF3 perovskite into a fluoride-rich ion/electron-conducting interphase for stable sodium metal anodes - Runzhi Xu; Yiqing Lu; Rui Ding; Yi Li; Weiming Li; Mingjun Xu; Tingyan Gu; Yuqi Liu; Chuyu Tan (Chemical Engineering Journal, 2026)

Chemical distance outweighs phylogeny in VOC-mediated cross-species plant defense communication - Chaonan Wang; Danfeng Liu; Xiao Xu; Mingjun Gao; Jiawei Wang; Jieren Jin; Yupeng Geng; Ruiting Ju; Yi Wang; Xiaoming Lu; Jihua Wu; Bo Li (Science China Life Sciences, 2026)

Formation of HREE-enriched ion-adsorption ore from LREE-rich granodiorite: a case study from the Meng Khun deposit, Laos - Mingjun Xie; Jian Zhou; Xueqiu Wang; Huohua Mo; Hanliang Liu; Jinfeng Bai; Xuemiao Du; Hui Wu (Mineralium Deposita, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

Sustainable pre-reduced sinter production: Recycling carbon-bearing dust and reducing CO2 emissions - Jing Wang; Xiduan Yang; Hui Xu; Laisheng Li; Boqi Wang; Jinliang Xiong; Xinyue Wu; Huibo Liu; Liangping Xu; Mingjun Rao (Journal of Cleaner Production, 2026)

Temperature mediates grazer effects on filamentous green algae proliferation: evidence from a macrophyte mesocosm experiment - Jian Gao; Anni Dai; Ming Wu; Yuhui Kang; Mingjun Liao; Zhengwen Liu; Erik Jeppesen (Hydrobiologia, 2026)

Electrostatic interaction induced enhancement of conductive hydrogel for motion detection and targeted identification of ascorbic acid in sweat - Jiarui Liu; Xianghe Zheng; Xinhang Yu; Mingjun Jia; Kai Wei; Liangjiu Bai; Wenxiang Wang; Kun Yin; Lixia Yang; Hou Chen (Analytica Chimica Acta, 2026)

Physicochemical determinants of macrophyte selection by Pomacea canaliculata and the implications for lake restoration - Yinwei Gao; Jian Gao; Anni Dai; Junzhan Li; Yunfei Zhou; Jiahe Zhu; Kaida Peng; Yachan Ji; Heyun Wang; Mingjun Liao; Zhengwen Liu; Erik Jeppesen (Aquatic Sciences, 2026)

A bimodal phenomenon in lake evolution since the last deglaciation from Qinghai-Tibet Plateau: Multiple hypothesis verification and a new mechanism - Zhansen Zhang; Yu Li; MingJun Gao; Hao Shang; Shiyu Liu; Jiarui Zhao; Tingting Xi; Wanchen Sun (Global and Planetary Change, 2026)

Molecular insights into whey protein fibril-sodium alginate-piperine complexes for stabilizing astaxanthin emulsions with improved bioaccessibility - Junquan Zheng; Daobang Tang; Xueming Liu; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Jingrong Cheng (Food Hydrocolloids, 2026)

Quality optimization and shelf-life prediction of braised beef using synergistic ε-polylysine-integrated sterilization technologies - Jingrong Cheng; Zhenhua Shi; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Food Control, 2026)

Novel insights into sulfide-enhanced nitritation with aerobic granular sludge - Manyu Qin; Mingjun Li; Chaowen Xie; Zengyi Li; Caixia Wang; Jianfang Wang; Feiyue Qian; Wenru Liu (Environmental Research, 2026)

Condensate gas adsorption and desorption behavior on continental shale matrix under retrograde condensation effect - Mingjun Chen; Maoling Yan; Yili Kang; Hua Liu; Xiaohu Hu; Gang Xiong; Zhehan Lai; Jiajia Bai (Chemical Engineering Journal, 2026)

Multilayer-like peptide-lipid nanoparticles enable effective p53 mRNA delivery for tumor suppression in non-small cell lung cancer - Zhe Wang; Weisi Yuan; Meiping Song; Mingjun Zhang; Chunpeng Yang; Weibang Xia; Jiao Chen; Yuhong Zhen; Yu Liu; Hongxu Liu; Yunming Wang; Yinan Zhao; et al. (Chemical Engineering Journal, 2026)

Identification of functional hotspots via hybrid nuclear magnetic Resonance-Computational strategy for directed evolution of large enzymes - Yihao Chen; Zhou Gong; Xiaoling Zhao; Ali Raza; Mingjun Zhu; Zhiqing Tao; Wenhui Li; Xu Zhang; Maili Liu; Lichun He (Bioresource Technology, 2026)

Mechanistic Insight into Formation and Release Enhancement of Sulindac-Amino Acid Small-Molecule Hydrogels - Jiaxin Chen; Huizhen Sun; Wuheng Yue; Zhimin Yue; Baimin Niu; Mingjun Li; Xinru Lu; Jue Wang; Xiaoqian Liu; Jiawei Han (Pharmaceutical Research, 2026)

Effects of low-molecular-weight organic acids and manganese-modified biochar application sequences on the environmental risk of soil cadmium and arsenic - Yongqiang Yang; Mingjun Li; Yipan Zhao; Liping Li; Yale Wang; Weiqin Xing; Chunhong Xu; Qipo Yang; Yali Wang; Yu Liu (Environmental Geochemistry and Health, 2026)

Intelligent trajectory tracking control for autonomous sailboats based on event-triggered NMPC and adaptive reference trajectory - Hongqiang Sang; Mingjun Jia; Xiujun Sun; Fen Liu; Yanhong Wang (Ocean Engineering, 2026)

Region tracking with smooth control inputs for AUVs based on a piecewise barrier-type function - Yingqi Yan; Xing Liu; Bo Geng; Mingjun Zhang (Ocean Engineering, 2026)

An AUV fault diagnosis method based on composite feature extraction and fusion from multi-sensor sequence chain graphs - You Zhang; Xing Liu; Ning Gai; Mingjun Zhang (Ocean Engineering, 2026)

Single adsorption and co-adsorption of aldehyde molecules over (111) surface of precious metal: A theoretical perspective evaluation - Zhengyun Zhang; Manmen Liu; Mingjun Peng; Kunhua Zhang; Xiaolong Zhou (Journal of Environmental Management, 2026)

Impact of readily biodegradable chemical oxygen demand on partial nitritation granules under high-salinity continuous-flow conditions - Mingjun Li; Xingyu Zhang; Manyu Qin; Chaowen Xie; Zengyi Li; Chengcheng Tong; Jianfang Wang; Feiyue Qian; Wenru Liu (Bioresource Technology, 2026)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

Multi-pulse seismic effect in regional scale landslide using an improved smoothed particle hydrodynamics method - Mingjun Zhou; Zhiyong Qi; Shun Dong; Yong Liu (Landslides, 2026)

Impacts of long-term fertilizer reduction and organic substitution on microbe-mediated multi-nutrient in agricultural ecosystems - Zhenling Li; Jiawei Ying; Xiaokang He; Yangyang Li; Guangchun Shan; Chenghong Feng; Mingjun Ding; Gaoxiang Huang; Jia Liu (Agriculture, Ecosystems & Environment, 2026)

Dynamic profiling of myogenesis in developing ovine skeletal muscle - Weiwei Duan; Zhenzhen Gu; Chenxi Liu; Wenrong Li; Sangang He; Bin Han; Lu Shi; Mingjun Liu (Meat Science, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Letting the catalyst take a break: Pulse-potential-driven mass transfer enhancement dominates efficient electrooxidation of ethylene glycol - Mingjun Ouyang; Yutong Liu; Lianchao Wang; Hua Wu; Kuaibing Wang (Chemical Engineering Journal, 2026)

Enhanced stability and bioavailability of astaxanthin via piperine co-encapsulation in whey protein fibril- sodium alginate complexes - Jingrong Cheng; Junquan Zheng; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Carbohydrate Polymers, 2026)

Impacts of the humid climate on the development of two ancient civilizations on the northeastern margin of the Qinghai–Xizang Plateau - Mingjun Gao; Yu Li; Tingting Xi; Jiarui Zhao; Zhansen Zhang; Junjie Duan; Yaxin Xue; Hao Shang; Shiyu Liu (Anthropocene, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

SERPINB1 promotes porcine deltacoronavirus replication by targeting the viral accessory protein NS7a - Junfang Yan; Xinru Liu; Huixin Zhu; Liang Li; Hongye Pan; Renjie Bao; Qiutian Li; Jing Sun; Houhui Song; Mingjun Su (Veterinary Microbiology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Spatial and climate dependency of water isotope fractionation between precipitation and vapor in East Asia based on explainable machine learning - Kun Liu; Shengjie Wang; Jinzhao Liu; Kei Yoshimura; Haixiang Jie; Yudong Shi; Shijun Lei; Yao Cheng; Liwei Wang; Mingjun Zhang (Global and Planetary Change, 2026)

The promising effects of bacterial and microalgal inoculants in enhancing tomato growth and improving soil quality - Tongtong Xu; Qixiang Xian; Yunqian Cui; Huali Pei; Wei Liu; Mingjun Chen; Jingling Liu; Hongbo Yu; Nortoji A. Khujamshukurov; Meimei Wu (Biocatalysis and Agricultural Biotechnology, 2026)

A dual-Bayesian network framework for assessing inland waterway shipping safety: A case study of the Yangtze river - Fang Wanwei; Ji Mingjun; Duan Yuqi; Liu Xiaojia (Ocean Engineering, 2026)

Contribution of oasis evapotranspiration to precipitation in arid Central Asia: Quantifying moisture recycling of mountain-oasis-desert systems - Haixiang Jie; Kun Liu; Shengjie Wang; Yudong Shi; Shijun Lei; Liwei Wang; Mingjun Zhang (Journal of Hydrology, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Stability assessment of CO2 hydrate-based sequestration in complex marine environments - Lei Zhang; Heng Liu; Xinyi Shan; Bingbing Chen; Mingjun Yang (Chemical Engineering Journal, 2026)

Biochar addition increases the soil active nitrogen fractions in abandoned grasslands in ecologically fragile areas - Shuainan Liu; Mingjun Xie; Guorong Xu; Wende Lu; Xinyue Zhang; Guang Li (Applied Soil Ecology, 2026)

Optimal monitoring time of kiwifruit orchard soil moisture content under irrigation using the red-edge indices acquired by UAV-based mutilspectral data - Mingjun Wang; Shidan Zhu; Shouzheng Jiang; Fei Chen; Xiuyun Yu; Lu Zhao; Zongjun Wu; Quanshan Liu; Ningbo Cui; Zhihui Wang; Liwen Xing (Computers and Electronics in Agriculture, 2025)

Development of a core streptavidin-bridging amplified ELISA based on p54 epitope for high-sensitivity detection of african swine fever virus antibodies - Jing Sun; Yingshan Zhou; Xingbo Liu; Xiaoxu Du; Jiongze Cheng; Huihua Zheng; Shuonan Pan; Junfang Yan; Xingdong Zhou; Xiaodu Wang; Zixiang Zhu; Dongbo Sun; et al. (The Veterinary Journal, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Disclosing occurrence of typical tire wear particle-derived chemicals in grassland soils from remote pastoral areas, north China - Guoguang Wang; Aoduo Yang; Shuaihao Liu; Mingjun Mo; Haiyue Chen; Guangzhi Rong; Haixia Wang; Yu Liu (Environmental Research, 2025)

Enhanced identification of novel pathogenic variants in hereditary hearing loss through physical phasing with integrated short and long-read sequencing data - Lu Kang; Qian Zhang; Chao Wang; Jia Geng; Xinlei Li; Mingjun Zhong; Sihan Liu; Xuegang Wang; Yu Lu; Jing Cheng; Yongxin Ma; Fengxiao Bu; et al. (Molecular Genetics and Genomics, 2025)

Study of 3D geological suitability evaluation via machine learning and gray correlation analysis - Xiaozheng Liu; Peng Zhang; Chang Xu; Dingfei Zhang; Zhaoxuan Dong; Mingjun Li (Earth Science Informatics, 2025)

Soil type-mediated root and leaf architectural modifications outweigh cadmium bioavailability in governing cadmium accumulation in rice - Gaoxiang HUANG; Jinbao ZHANG; Changfeng DING; Zhongyang XIONG; Jia LIU; Jingru HE; Haoyuan LÜ; Mingjun DING; Peng WANG; Yinghui JIANG; Lijun ZHOU; Zhenling LI (Pedosphere, 2025)

Mapping leaf water isotopes across China using precipitation isotope and climate data - Kun Liu; Shengjie Wang; Yuqing Qian; Jinzhao Liu; Hongyang Li; Yudong Shi; Shijun Lei; Athanassios A. Argiriou; Mingjun Zhang (Journal of Hydrology, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Application of density functional theory methods for evaluating the adsorption capacity of carbonyl sulfide and sulfur dioxide on pristine and transition metal doped Ag(111) surfaces - Zhengyun Zhang; Manmen Liu; Mingjun Peng; Kunhua Zhang; Xiaolong Zhou (Journal of Environmental Chemical Engineering, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Miconazole activates MAPK-driven oligodendrogenesis to promote myelin regeneration and neurological recovery after subarachnoid hemorrhage - Gao Mingjun; Xu Ruxiang; Liu Ping; Liu Lingtong; Hu Xiao; Wang Qi; Zou Jiangli; Yin Cheng (Chemico-Biological Interactions, 2025)

Thresholds for the relationships between soil trace elements and ecosystem multifunctionality in degraded alpine meadows - Yuping Wu; Mingjun Ding; Hua Zhang; Tiane Zou; Peng Huang; Huan Xu; Yueju Zhang; Huan Zeng; Jiaxin Xiong; Liyao Cheng; Linshan Liu; Yili Zhang (Agriculture, Ecosystems & Environment, 2025)

Leaf spot of yam caused by Schizophyllum commune in China - Ruifei Wang; Xuejia Wang; Liping Zhan; Xueyang Ren; Haibing Li; Yulong He; Hao Zhang; Yongkang Liu; Mingjun Li; Guixiao La; Qingxiang Yang (Australasian Plant Pathology, 2025)

Promotion of grain growth via solvent fumigation for wide-bandgap perovskite solar cells with low VOC deficit and perovskite/TOPCon tandem solar cells with efficiency >30% - Xiang Liao; Yuanfang Zhang; Zijian Qu; Qiang Zeng; Mingjun Zhang; Jungan Wang; Yining Pan; Jie Yang; Damin Zheng; Zengsheng Liu; Linhong Li; Menglei Xu; et al. (Science Bulletin, 2025)

Unveiling microbial mechanisms for fluoride and nutrient removal in iron-carbon constructed wetlands under micro-oxygen regulation - Mingjun Li; Shiyuan Wei; Xin Zhao; Jian Zhang; Zizhang Guo; Huaqing Liu; Haiming Wu (Journal of Hazardous Materials, 2025)

Positive Matrix Factorization (PMF) based on geochemical data for revising geological map in semi-desert covered terrains: A case study from a map sheer of Urat Rear Banner, Inner Mongolia, China - Yanling Sun; Xueqiu Wang; Hanliang Liu; Jian Zhou; Mingjun Xie (Geochemistry, 2025)

Revealing the aging-induced chemical and microstructure evolution of asphalt via AFM-IR and quantum chemistry simulation - Mingjun Hu; Shize Ji; Mingchen Li; Liyuan Liu; Huailei Cheng (Fuel, 2025)

Versatile defect-laden boronizing hard carbon for superior sodium-ion battery efficacy - Jiayi Wen; Cheng Liu; Mingjun Jing; Dan Li; Honghui Hu; Huaxin Liu; Tianjing Wu; Lanhua Yi; Yong Pei; Xue Zhong; Wentao Deng; Guoqiang Zou; et al. (Chemical Engineering Journal, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Toad’s survivability and soil microbiome alterations impacted via individual abundance - Tian Zhang; Yang Liu; Junde Li; Mingjun Yuan; Chunhan Qiao; Xiao Huang; Xueyao Yang; Bo Gao; Chuan Lou; Yan Yang; Yu Cao (Biologia Futura, 2025)

Weak Fault Feature Extraction for AUV Thrusters with Multi-Input Signals - Dacheng Yu; Feng Yao; Yan Gao; Xing Liu; Mingjun Zhang (Journal of Marine Science and Engineering, 2025)
This paper investigates weak fault feature extraction in AUV thrusters under multi-input signal conditions. Conventional methods often rely on insufficient input signals, leading to a non-monotonic mapping between fault features and fault severity. This, in turn, makes accurate fault severity identification infeasible. To overcome this limitation, this paper increases the number of input signals by utilizing all available measurable signals. To address the problems arising from the expanded signal set, a signal denoising method that combines Feature Mode Decomposition and wavelet denoising is proposed. Furthermore, a signal enhancement technique that integrates energy operators and the Modified Bayes method. Additionally, distinct technical approaches for noise reduction and enhancement are specifically designed for different input signals. Unlike conventional methods that extract features directly from raw input signals, for fault feature extraction and fusion, this study transforms the signals into the time, frequency, and time–frequency domains, extracting diverse fault features across these domains. A sensitivity factor selection method is then employed to identify the sensitive features. These selected features are subsequently fused using Dempster–Shafer evidence theory to construct the final fault feature. Finally, fault severity identification is carried out using the classical grey relational analysis. Pool experiments using the “Beaver II” AUV prototype validate the effectiveness of the proposed method.

Evaluation of the management of rotator cuff injuries utilising superparamagnetic iron oxide tracking stem cells - Ziang Cheng; Dianwei Liu; Jin-Young Park; Xiangji Meng; Yuxia Yang; Mengbo Dang; Xiaomei Dai; Jian Yang; Meijuan Yuan; Mingjun Li; Liang Wang; Yao Huang; et al. (Tissue and Cell, 2025)

Ameliorating canopy urban heat island in block level: A holistic investigation into the radius, form, and typologies - Sitao Li; Jingyan Zhang; Qiankun Xiao; Ke Fang; Sijie Ha; Huosheng Liu; Mingjun Teng; Xuefei Wu; Changguang Wu (Building and Environment, 2025)

Monsoon marginal zone’s dry/wet status and their links with tropical ocean–atmosphere interactions during the Holocene - Yu Li; Zhansen Zhang; Mingjun Gao; Junjie Duan; Yaxin Xue; Hao Shang; Shiyu Liu (Science Bulletin, 2025)

Improved motion planning for underactuated marine robots based on lateral error reconstruction - Bo Geng; Xing Liu; Manhui Zhang; Mingjun Zhang (Ocean Engineering, 2025)

Experimental studies on the correlations of male respiratory parameters with their body composition - Yi Xu; Lijuan Wang; Haitang Liu; Mingming Zhai; Mingjun Zhang; Haiguo Yin; Minzhou Chen (Energy and Buildings, 2025)

In situ constructing artificial interfacial layer enables dendrite-free zinc anode in aqueous batteries - Canglong Li; Changding Wang; Jie Huang; Qiwen Zhao; Wen Liu; Yuxuan Song; Mingjun Rao; Fu Wan; Yuejiao Chen; Weigen Chen; Shuhui Sun (Chemical Engineering Journal, 2025)

Experimental research on the influence of wall effect on the structure of cumulated semi-cokes - Zhouzijing Yang; Peibin Zhang; Liying Zhang; Yuxiu Zhang; Xiangang Liu; Yuqiu Zhang; Haibo Gao; Yongqi Liu; Mingjun Sun; Yanxia Wang (Process Safety and Environmental Protection, 2025)

Enhancing hydrological model performance through multi-source open-data utilization in the highly managed, data-scarce basin - Jiayan Zhang; Zhihong Liu; Yu Li; Yanhong Dou; Mingjun Wang; Huicheng Zhou; Bo Xu (Journal of Hydrology, 2025)

The role of clay in hydrate-based carbon emission reduction: Phenomenon, mechanisms, and application - Huiquan Liu; Shuai Wang; Yixuan Fu; Changrui Shi; Yongchen Song; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Comparative effects of 6PPD and 6PPD-Quinone at environmentally relevant concentrations on hepatotoxicity, glucolipid metabolism and ferroptotic response in adult zebrafish - Zhe Wang; Mingjun Zhu; Yao Hu; Jiaxi Liu; Xiaoyu Ma; Hong Zhou (Environmental Research, 2025)

Elucidating the co-metabolism mechanism of 4-chlorophenol and 4-chloroaniline degradation by Rhodococcus through genomics and transcriptomics - Yonglin Bo; Yixue Niu; Mingjun Zhu; Yaru Wang; Yu Wang; Yuhua Su; Qiyou Liu; Gang Wang; Yongqiang Wang (Environmental Research, 2025)

Enhanced nitrogen removal in constructed wetlands filled with iron-carbon substrates: Reexploring unique roles of iron-cycling and electroactive microorganisms - Mingjun Li; Shiyuan Wei; Ruigang Wang; Xin Zhao; Peihao Yan; Jian Zhang; Huaqing Liu; Zhen Hu; Haiming Wu (Journal of Environmental Management, 2025)

Self-Reconstruction of ultralow-Pt-loading Co3O4 nanoneedle array cathode for high-performance Li-O2 battery - Yong Liu; Mingjun Han; Jianye Liu; Yaling Huang; Yisi Liu; Wenzhang Li; Yang Liu; Jie Li (Chemical Engineering Journal, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Adaptive trajectory tracking control for underwater vehicle based on hierarchical compensation - Xing Liu; Tong Wang; Baoji Yin; Feng Yao; Mingjun Zhang (Ocean Engineering, 2025)

Impact of sewage sludge biochar spheres as constructed wetland substrates on antibiotic removal and application - Mingjun Zhong; Ze Zhang; Jialiang Zhang; Zihao Luo; Yunxian Chen; Mengxue Liu; Beini Gong; Hongcan Cui; Lihua Cui (Journal of Environmental Management, 2025)

Insights and simulation models for long-distance water jet mining: Evolution of breaking depth and mass - Mingjun Jiang; Biao Sun; Yue Niu; Yingke Liu; Zhaoxi Long; Xiangyang Bu (Process Safety and Environmental Protection, 2025)

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Male mites are the promising targets for control of Dermanyssus gallinae (Acari: Dermanyssidae) based on the reproductive biology research - Boxing Liu; Jiaqi He; Qi Liu; Bohan Wang; Mingjun Xiong; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2025)

Selection and validation of reference genes for the normalization of RT-qPCR gene expression data in Rheum tanguticum (Polygonaceae) under various abiotic stresses - Mingjun Yu; Jiarui Jin; Xiaoli Li; Yuping Liu; Xu Su; Marcos A. Caraballo-Ortiz; Penghui Zhang; Qian Yang; Rongju Qu; Zhaxi Cairang; Xuanlin Gao; Yinghui Zheng (Journal of Plant Physiology, 2025)

Rapid formation of carbon dioxide hydrate governed by the natural nano-clay for effective carbon dioxide capture - Huiquan Liu; Shuai Wang; Changrui Shi; Yongchen Song; Yixuan Fu; Zhen Li; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Facile and green synthesis of Ag/Cu bimetallic nanoparticles using waste banana peel extract for effective corrosion inhibition of mixed sulfate-reducing bacteria - Yuhua Su; Fuli Wu; Peng Xiao; Hang Zhang; Guanglei Lv; Mingjun Zhu; Qiyou Liu; Chaocheng Zhao (Journal of Environmental Management, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Oxidation and nitrosation in Cantonese sausage during processing and storage-The impact of adding Prunus mume polyphenol - Jingrong Cheng; Peiyu Chen; Xueming Liu; Daobang Tang; Huaigu Yang; Mingjun Zhu (Food Control, 2025)

Thermodynamic and kinetic properties of gas hydrate phase transition from formation to decomposition with applications: A review - Zheyuan Liu; Xiaoyang Liu; Mingjun Yang; Weixin Pang; Binlin Dou; Yongchen Song (Journal of Environmental Chemical Engineering, 2024)

Visual study of hydrate particles agglomeration and rolling characteristic in gas-oil-water phase using a flow loop - Zheyuan Liu; Shichen Shen; Binlin Dou; Ni Liu; Liang Yang; Mingjun Yang; Yongchen Song (Fuel, 2024)

Enhancing the anti-fatigue effect of ginsenoside extract by Bifidobacterium animalis subsp. lactis CCFM1274 fermentation through biotransformation of Rb1, Rb2 and Rc to Rd - Xin Tang; Cencen Liu; Bulei Wang; Mingjun Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui (Food Bioscience, 2024)

The peculiar role of iodides and formation of iodinated oligomer byproducts upon phenol mineralization with boron-doped diamond anode - Ruochen Liu; Mingjun Ouyang; Shujuan Chen; Saier Wang; Chenwei Liu; Chunyong Zhang; Hua Wu (Chemical Engineering Journal, 2024)

Phase-Field Simulation of Counter-Current Imbibition and Factors Influencing Recovery Efficiency - Liu Yang; Mingjun Li; Haitao Zhang; Yan Liu; Zhaoyang Liu; Zhengyan Zhang; Fei Gong; Suling Wang (Transport in Porous Media, 2024)

Stress Distribution and Dynamic Evolution of Coal Surface Under a Single Droplet of Discrete Water Jet - Man Yuan; Xun Zhao; Mingjun Jiang; Yingke Liu; Fengchao Wang; Tengrui Yang; Lingxiao Yin; XiaoJiang Wen (Rock Mechanics and Rock Engineering, 2024)

Exploration of the Formation Mechanism of Underground Brine Based on Hydrodynamic Environment Analysis Using Grain-Size Data of One Drilling Core - Qiao Su; Ying Yu; Mingjun Chen; Tengfei Fu; Wenzhe Lyu; Wenquan Liu (Journal of Marine Science and Engineering, 2024)
The Laizhou Bay area in China harbors a significant amount of Quaternary brine resources, which have been gradually depleted due to intensive long-term exploitation. It is widely accepted that underground Quaternary brine in Laizhou Bay originates from seawater. However, there are disputes regarding the specific form of seawater concentration and the geological processes leading to brine formation. Revealing the genesis of shallow brine in different geological environments is of great scientific significance for resource production and environmental protection. This study analyzed the hydrodynamic conditions of underground brine and adjacent strata based on grain size data, and the possible formation mechanisms of brine layers at different depths were discussed. The mineralization of underground brine is a complex process controlled by various factors, such as specific meteorological and paleogeographic environments, topography, and hydrogeological conditions. On the southern coast of Laizhou Bay, there are three ways in which underground brine layers are formed: residual evaporation from lagoons during the initial regression stage, the hypersaline zone in estuarine lagoons during high-sea-level periods, and brine formation from seawater evaporation on intertidal flats. Turbulent sea–land interactions and the development of river deltas are also necessary conditions for brine mineralization, as they are favorable for replenishing, transporting, and storing underground brine layers.

Refining habitat selection for sulfate-reducing bacteria: Evaluating suitability and adaptability for sulfate-metal wastewater treatment during anaerobic-to-aerobic transitions - Zhendong Yang; Jing Wang; Qihong Wu; Zhaoyue Yang; Tuan Liu; Li Zeng; Zhaogang Lin; Mingjun Li; I.A. Ibrahim; Huaqun Yin; Zhenghua Liu (Journal of Environmental Management, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Spatiotemporal distribution characteristics of fracturing fluid in multiscale pore structure of deep marine shale gas reservoirs - Peisong Li; Mingjun Chen; Yili Kang; Hua Liu; Sidong Fang; Lijun You; Zhehan Lai; Yeyu Zou (Fuel, 2024)

Defective carbon-bridged Cu sites to boost oxygen reduction reaction in neutral zinc-air batteries - Tianjing Wu; Honghui Hu; Yufeng Wu; Mingjun Jing; Zhanpeng Chen; Fang Chen; Yansong Bai; Dan Li; Sheng Zhang; Lijie Liu; Wentao Deng; Hongshuai Hou; et al. (Chemical Engineering Journal, 2024)

Scalable MXene/Sepiolite film-based hydrovoltaic generators with outstanding output power - Weijing Yuan; Huiquan Liu; Yixuan Fu; Yang Zhang; Haoqi Huo; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Grifola frondosa polysaccharide's therapeutic potential in oxazolone-induced ulcerative colitis - Xiaoyi Liu; Mingjun Zhang; Shuai Chen; Huijuan Liu; Haoran Ma; Ting Hu; Peng Luo; Shaofeng Wei (Carbohydrate Polymers, 2024)

Synergistic effects of mixed microorganisms on the corrosion of X65 carbon steel in actual reinjection water - Yuhua Su; Hang Zhang; Guanglei Lv; Fuli Wu; Peng Xiao; Mingjun Zhu; Chaocheng Zhao; Qiyou Liu (Journal of Environmental Chemical Engineering, 2024)

Enhancement of power density and hydrogen productivity of the reverse electrodialysis process by optimizing the temperature gradient between the working solutions - Xi Wu; Youwen Zhang; Dexin Sun; Yibo Lv; Mingjun Liu; Xiaojing Zhu (Chemical Engineering Journal, 2024)

Lightning characteristics and associated microphysical parameters in a strong thunderstorm with an extreme gale - Yan Liu; Fanchao Lyu; Mingjun Wang; Wei Xu; Du Xi; Sulin Jiang (Natural Hazards, 2024)

Quantification of irrigation water transport processes in ZiZiphus jujuba garden using water stable isotopes - Xiaofei Zhong; Mingjun Zhang; Cunwei Che; Zechen Liu; Beibei Li; Yuanyuan Zhang (Journal of Mountain Science, 2024)

Effect of dietary vitamin D3 on growth performance and functional homeostasis of particular intestinal segments in grass carp fingerlings - Hao Sun; Pei Ge; Jiaxi Liu; Dan Xiong; Mingjun Zhu; Hong Zhou (Aquaculture International, 2024)

Synthesis, Structure and Luminescence Properties of Mn-doped MgAl2O4 Red-Emitting Phosphors with Varying Sintering Temperature - Jiahao Zha; Chongjun He; Fangzhou Chen; Hongwei Wang; Biao Dong; Lijuan Liu; Mingjun Xia; Chenguang Deng; Qian Li; Yuangang Lu; Huiting Chen (Journal of Fluorescence, 2024)

The entropy effect on the structure and microwave dielectric properties of high-entropy Lix(MgZnCoNi)(1-x)/4Al2O4-δ ceramics - Mingjun Xie; Yuanming Lai; Pingwen Xiang; Feng Liu; Linqiao Zhang; Xingyue Liao; Huan Huang; Qian Liu; Chongsheng Wu; Yuanxun Li (Chemical Engineering Journal, 2024)

Copper induces cytotoxicity in freshwater bivalve Anodonta woodiana hemocytes - Mingjun Yan; Xiubao Chen; Tao Jiang; Junren Xue; Karsten Liber; Hongbo Liu; Jian Yang (Chemosphere, 2024)

Loss of Gcn2 exacerbates gossypol induced oxidative stress, apoptosis and inflammation in zebrafish - Mingjun Tang; Weiyi Xia; Fei Song; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2024)

Reduced internal stress of quasi-single crystalline Na4Fe3(PO4)2P2O7 electrode enhancing sodium-ion kinetics - Yukun Xi; Mingjun Wang; Guangjin Wang; Junqi Peng; Ningjing Hou; Zihao Yang; Xiaoxue Wang; Dongzhu Liu; Xiaohua Pu; Guiqiang Cao; Ruixian Duan; Qinting Jiang; et al. (Chemical Engineering Journal, 2024)

Biodegradation characteristics of p-Chloroaniline and the mechanism of co-metabolism with aniline by Pseudomonas sp. CA-1 - Mingjun Zhu; Yuhua Su; Yaru Wang; Yonglin Bo; Yufeng Sun; Qiyou Liu; Hang Zhang; Chaocheng Zhao; Yingying Gu (Bioresource Technology, 2024)

Depositional process and sediment dispersal pattern of mass transport complex on a slope with numerous elliptical depressions, northwestern South China Sea - Chao Liang; Chiyang Liu; Xinong Xie; Xiaohang Yu; Lei Huang; Jie Pan; Yunlong He; Hui Chen; Dongmei Tian; Honggang Mi; Mingjun Li; Hui Zhang (Sedimentary Geology, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Enhancing precision of root-zone soil moisture content prediction in a kiwifruit orchard using UAV multi-spectral image features and ensemble learning - Shidan Zhu; Ningbo Cui; Li Guo; Huaan Jin; Xiuliang Jin; Shouzheng Jiang; Zongjun Wu; Min Lv; Fei Chen; Quanshan Liu; Mingjun Wang (Computers and Electronics in Agriculture, 2024)

The efficient uptake of uranium by amine-functionalized β-cyclodextrin supported fly ash composite from polluted water - Congcong Chen; Xuan Liu; Xiaoyu Tian; Jiaqi Feng; Yujia Liu; Mingjun Song; Wenkun Zhu; Yong Zhang (Science of The Total Environment, 2024)

Effect of various phosphorus levels on the extraction of Cd, the transformation of P, and phosphorus-related gene during the phytoremediation of Cd contaminated soil - Hongli Huang; Rule Zhao; Guanlin Guo; Yinhai He; Shuofu Chen; Yichun Zhu; Mingjun Xiao; Ping Liu; Junwu Liu; Yingchun Fang; Yaoyu Zhou (Environmental Research, 2024)

Reconstruction of Historical Metal Backgrounds in Lacustrine Environments of China Using an Anodonta woodiana “Specimen Bank” - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Particle sizes crucially affected the release of additives from tire wear particles during UV irradiation and mechanical abrasion - Taishuo Zhang; Mingjun Wang; Yingxuan Han; Jingxuan Liu; Zixuan Zhang; Mengjie Wang; Peng Liu; Shixiang Gao (Journal of Hazardous Materials, 2024)

Effects of particle size and AQDS on the flow of electron equivalents between magnetite and aqueous Fe2+ - Huan Peng; Zhenli Zhu; Carolyn I. Pearce; Anxu Sheng; Mingjun Nie; Alpha T. N'Diaye; Xin Zhang; Kevin M. Rosso; Juan Liu (Geochimica et Cosmochimica Acta, 2024)

Effects of the invasive red swamp crayfish (Procambarus clarkii) on eelgrass-dominated clearwater lakes: the role of bioturbation - Jian Gao; Hong Yuan; Hui Zhang; Mingjun Liao; Heyun Wang; Yuhui Kang; Zhengwen Liu; Erik Jeppesen (Hydrobiologia, 2024)

Enhancing tetracycline degradation with biomass carbon quantum dot (CQDs)-modified magnetic heterojunction CeO2-Fe3O4 under visible light - Hua Chai; Ze Zhang; Jie Sun; Mingjun Zhong; Mengxue Liu; Jing Li; Zihao Chen; Beini Gong; Qiaoling Xu; Zhujian Huang; Lihua Cui (Journal of Environmental Chemical Engineering, 2024)

Performance evaluation of rhamnolipid biosurfactant produced by Pseudomonas aeruginosa and its effect on marine oil-spill remediation - Mingjun Zhu; Hang Zhang; Wu Cui; Yuhua Su; Shuo Sun; Chaocheng Zhao; Qiyou Liu (Archives of Microbiology, 2024)

Interannual variations in stable isotopes of atmospheric water in arid Central Asia due to changes in atmospheric circulation - Shengjie Wang; Gahong Yang; John Bershaw; Xiaokang Liu; Kei Yoshimura; Yanqiong Xiao; Mingjun Zhang (Global and Planetary Change, 2024)

Fault feature extraction method for AUV thruster based on two-stage fusion from multi-source information - Ning Gai; Mingjun Zhang; Xing Liu (Ocean Engineering, 2024)

Predicting vessel arrival times on inland waterways: A tree-based stacking approach - Jinyu Lei; Zhong Chu; Yong Wu; Xinglong Liu; Mingjun Luo; Wei He; Chenguang Liu (Ocean Engineering, 2024)

Effects of herbicide butachlor application on the growth of periphytic biofilms and nitrogen loss in paddy systems - Yanhui ZHAO; Mingjun LEI; Liandong JING; Fan XIA; Meixia YAN; Jiantong LIU; Yonghong WU; Yunli WU; Chenxi WU (Pedosphere, 2024)

Application of bacterial agent YH for remediation of pyrene-heavy metal co-pollution system: Efficiency, mechanism, and microbial response - Yuhua Su; Mingjun Zhu; Hang Zhang; Hongxu Chen; Jiguo Wang; Chaocheng Zhao; Qiyou Liu; Yingying Gu (Journal of Environmental Management, 2024)

The effects of rhamnolipid on the formation of CH4 hydrate and separation of CH4/N2 via hydrate formation - Yi Zhang; Jingru Zhang; Xingang Xu; Wanting Liu; Yongsheng Xu; Mingjun Yang; Yongchen Song (Fuel, 2024)

Copper Stress Causes Shell Morphology Changes in Early Juvenile Anodonta woodiana Based on Geometric–Morphometric Analysis - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Tao Jiang; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Characteristic microbiome and synergistic mechanism by engineering agent MAB-1 to evaluate oil-contaminated soil biodegradation in different layer soil - Yaru Wang; Shuo Sun; Qiyou Liu; Yuhua Su; Hang Zhang; Mingjun Zhu; Fang Tang; Yingying Gu; Chaocheng Zhao (Environmental Science and Pollution Research, 2024)

Achieving tunable time-dependent delayed emission color via dynamic competition between the matrix and carbon dots for anti-counterfeiting and multidimensional encryption - Yufeng Chang; Nian Fu; Mingjun Chen; You Zhang; Fuxing Li; Zhenyang Liu; Fenghe Wang; Gang Yue; Xu Li; Li Guan (Chemical Engineering Journal, 2024)

Enhanced radiation heat transfer performance of Alumina-Spinel composite sphere with hollow structure for rapidly ultra-high temperature thermal storage/release process - Xin Zhou; Shenghao Liao; Seiji Yamashita; Mitsuhiro Kubota; Akihiro Takeuchi; Peng Gao; Mingjun Liu; Ruoxuan Li; Chaoyang Zhang; Hideki Kita (Chemical Engineering Journal, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

Command-Filter-Based Region-Tracking Control for Autonomous Underwater Vehicles with Measurement Noise - Tu Lv; Yujia Wang; Xing Liu; Mingjun Zhang (Journal of Marine Science and Engineering, 2023)
This paper investigates the AUV region-tracking control problem with measurement noise and transient and steady-state constraints. To achieve the fluctuation of AUV tracking error within an expected region while satisfying the transient and steady-state performance constraints, this paper proposes an improved nonlinear tracking error transformation method. This method converts the tracking error into a new virtual error variable through nonlinear conversion, thus transforming the above performance requirements for the tracking error into boundedness requirements for the new virtual error variable. In addition, aiming at the problem of measurement noise causing strong fluctuation of the control signal, this paper proposes a finite-time AUV control method based on a two-stage command filter. This method utilizes a finite-time sliding mode differentiator to filter the virtual control signal during the derivation of the control law using the backstepping technique. In light of the signal loss incurred by two-stage filtering and its potential impact on system stability, a finite-time compensator is designed to compensate the signal loss and achieve finite-time stability of the closed-loop system. Finally, simulations conducted using ODIN AUV demonstrate that the proposed method exhibits smooth control signal and low energy consumption characteristics. Furthermore, the tracking error meets the requirements for both transient and steady-state performance, as well as regional tracking.

Where and how to cool through blue infrastructure? Large lake groups to ameliorate urban overheating in a typical inland multi-lake megacity - Yatian Cheng; Carlos Bartesaghi-Koc; Yu Tian; Lidu Shen; Mingjun Teng; Huosheng Liu; Zhiyan Xiao; Bin Zhang; Changguang Wu (Sustainable Cities and Society, 2023)

Adaptive fault tolerant control scheme based on observer-controller integrated design for deep-sea vehicles - Xing Liu; Qixing Lu; Bo Geng; Mingjun Zhang; Baoji Yin (Ocean Engineering, 2023)

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

SARS-COV-2 spike protein promotes RPE cell senescence via the ROS/P53/P21 pathway - Yuhang Zhang; Xuyan Peng; Mengjiao Xue; Jingjing Liu; Guohui Shang; Mingjun Jiang; Dandan Chen; Baixue Liu; Yuxuan Wang; Xiaolin Jia; Jianqing Xu; Fengyan Zhang; et al. (Biogerontology, 2023)
SARS-Cov-2 infection, which has caused the COVID-19 global pandemic, triggers cellular senescence. In this study, we investigate the role of the SARS-COV-2 spike protein (S-protein) in regulating the senescence of RPE cells. The results showed that administration or overexpression of S-protein in ARPE-19 decreased cell proliferation with cell cycle arrest at the G1 phase. S-protein increased SA-β-Gal positive ARPE-19 cells with high expression of P53 and P21, senescence-associated inflammatory factors (e.g., IL-1β, IL-6, IL-8, ICAM, and VEGF), and ROS. Elimination of ROS by N-acetyl cysteine (NAC) or knocking down p21 by siRNA diminished S-protein-induced ARPE cell senescence. Both administrated and overexpressed S-protein colocalize with the ER and upregulate ER-stress-associated BIP, CHOP, ATF3, and ATF6 expression. S-protein induced P65 protein nuclear translocation. Inhibition of NF-κB by bay-11-7082 reduced S-protein-mediated expression of senescence-associated factors. Moreover, the intravitreal injection of S-protein upregulates senescence-associated inflammatory factors in the zebrafish retina. In conclusions, the S-protein of SARS-Cov-2 induces cellular senescence of ARPE-19 cells in vitro and the expression of senescence-associated cytokines in zebrafish retina in vivo likely by activating ER stress, ROS, and NF-κb. These results may uncover a potential association between SARS-cov-2 infection and development of AMD.

Spatial variations, health risk assessment, and source apportionment of soil heavy metals in the middle Yellow River Basin of northern China - Futian Liu; Xueqiu Wang; Shuang Dai; Jian Zhou; Dongsheng Liu; Qinghai Hu; Wei Wang; Mingjun Xie; Yuexin Lu; Mi Tian; Hao Yan (Journal of Geochemical Exploration, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

4.3% efficient kesterite solar cell modules - Mingjun Yuan; Chunxu Xiang; Zhen Yan; Hongfei Zhou; Naiyun Liu; Shuxia Wei; Wei Li; Weibo Yan; Chunlei Yang; Hao Xin (Science Bulletin, 2023)

N-doped porous carbon-anchored zinc single-atom as an efficient and robust heterogeneous catalyst for glycerol carbonylation with urea - Jinghui Shi; Yunzuo Cui; Hao Sun; He Wang; Chunling Liu; Xiangxin Xue; Chuanbi Li; Longlong Geng; Jingyao Liu; Mingjun Jia (Chemical Engineering Journal, 2023)

Manganese-based flow battery based on the MnCl2 electrolyte for energy storage - Yuqin Liu; Mingjun Nan; Zichao Zhao; Bo Shen; Lin Qiao; Huamin Zhang; Xiangkun Ma (Chemical Engineering Journal, 2023)

A model based on immune-related lncRNA pairs and its potential prognostic value in immunotherapy for melanoma - Wenshuai Li; Yingxuan Zhan; Chong Peng; Zhan Wang; Tiantian Xu; Mingjun Liu (Functional & Integrative Genomics, 2023)

Surfactant-enhanced bioremediation of petroleum-contaminated soil and microbial community response: A field study - Hao Ling; Jinyu Hou; Mingjun Du; Yun Zhang; Wuxing Liu; Peter Christie; Yongming Luo (Chemosphere, 2023)

Chinese yam (Dioscorea): Nutritional value, beneficial effects, and food and pharmaceutical applications - Ye Li; Shengyang Ji; Tao Xu; Yongheng Zhong; Minghao Xu; Yuqi Liu; Mingjun Li; Bei Fan; Fengzhong Wang; Jianbo Xiao; Baiyi Lu (Trends in Food Science & Technology, 2023)

Ti-doped Zr-UiO-66-NH2 boosting charge transfer for enhancing the synergistic removal of Cr (VI) and TC-HCl in wastewater - Yue Gao; Yuting Huang; Mingjun Bao; Xin Zhang; Xiaoxue Zhou; Lexin Liu; Zhiguang Zhang; Libin Zeng; Jun Ke (Process Safety and Environmental Protection, 2023)

A post-synthetic modified NH2-MIL-125 (Ti) catalyst for boosting photochemical Cr (VI) reduction - Xin Zhang; Yuting Huang; Mingjun Bao; Yue Gao; Xiaoxue Zhou; Lexin Liu; Ye Hu; Zhiguang Zhang (Process Safety and Environmental Protection, 2023)

Zonotopic resilient state estimation for unmanned surface vehicles subject to integrity attacks - Jitao Li; Yujia Wang; Xing Liu; Feng Yao; Mingjun Zhang (Ocean Engineering, 2023)

Experimental study on boiling two-phase of liquid sodium along a 7-rod bundle – Part Ⅰ: Pressure drop characteristics - Yandong Hou; Liu Wang; Kui Zhang; Mingjun Wang; Yingwei Wu; Wenxi Tian; Suizheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Experimental study on boiling two-phase of liquid sodium along a 7-rod bundle – Part Ⅱ: Heat transfer characteristics - Yandong Hou; Liu Wang; Kui Zhang; Mingjun Wang; Yingwei Wu; Wenxi Tian; Suizheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Introduction of the FecG mutation in GDF9 gene via CRISPR/Cas9 system with single-stranded oligodeoxynucleotide - Xin Xu; Xuemei Zhang; Xinrong Peng; Chunjie Liu; Wenrong Li; Mingjun Liu (Theriogenology, 2023)

Release of millions of micro(nano)plastic fragments from photooxidation of disposable plastic boxes - Fugeng Zha; Jiamin Dai; Yinxuan Han; Peng Liu; Mingjun Wang; Haiyong Liu; Xuetao Guo (Science of The Total Environment, 2023)

How to use lake breeze circulations to improve urban natural ventilation: A case study in a typical inland multi-lake megacity - Yatian Cheng; Lidu Shen; Mingjun Teng; Huosheng Liu; Weijin Cheng; Bin Zhang; Changguang Wu (Landscape and Urban Planning, 2023)

Molecular-micron multiscale toughening and flame retarding for polyurethane foams - Furong Zeng; Xiaofeng Men; Mingjun Chen; Bowen Liu; Qingwen Han; Shengchao Huang; Haibo Zhao; Yuzhong Wang (Chemical Engineering Journal, 2023)

Synthesis and enhancement of carbon quantum dots from Mopan persimmons for Fe3+ sensing and anti-counterfeiting applications - Haotian Ma; Li Guan; Mingjun Chen; You Zhang; Yue Wu; Zhenyang Liu; Dawei Wang; Fenghe Wang; Xu Li (Chemical Engineering Journal, 2023)

Exposure-lag response of fine particulate matter on intrauterine fetal death: an analysis using a distributed lag non-linear model in Linxia Hui Autonomous Prefecture, China - Wenshan Yan; Mingjun Xie; Xinwei Liu; Shiqiang Han; Juanjuan Xu; Gexiang Zhang (Environmental Science and Pollution Research, 2023)

N-nitrosamines-mediated downregulation of LncRNA-UCA1 induces carcinogenesis of esophageal squamous by regulating the alternative splicing of FGFR2 - Xianghu Wang; Mingjun Sun; Zhikui Gao; Lihong Yin; Yuepu Pu; Yong Zhu; Xiaobin Wang; Ran Liu (Science of The Total Environment, 2023)

Quantifying food loss along the animal products supply chain in China with large-scale field-survey based primary data - Ruigang Wang; Gang Liu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Shijun Lu; Mingjun Zhao; Huiwu Sun; Chuang Ma; Guangyan Cheng (Resources, Conservation and Recycling, 2023)

Pyrolytic aerogels with tunable surface groups for efficient methane solidification storage via gas hydrates - Changrui Shi; Shuai Wang; Huiquan Liu; Lunxiang Zhang; Mingjun Yang; Yongchen Song; Jiafei Zhao; Zheng Ling (Fuel, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

Estimation of Lightning-Generated NOx in the Mainland of China Based on Cloud-to-Ground Lightning Location Data - Qi Li; Fengxia Guo; Xiaoyu Ju; Ze Liu; Mingjun Gan; Kun Zhang; Binbin Cai (Advances in Atmospheric Sciences, 2023)

Host Fish Suitability for Freshwater Bivalve Anodonta woodiana Breeding Programs - Xiubao Chen; Guochao Duan; Mingjun Yan; Hongbo Liu; Tao Jiang; Jian Yang (Fishes, 2022)
The freshwater bivalve Anodonta woodiana is native to China and widely distributed in Asia, Europe, and North America. However, natural populations of A. woodiana in China have dramatically declined recently. Several fish species have been used as potential hosts in breeding programs; nonetheless, the optimal host species is yet to be identified. In this study, we examined the suitability of five potential host fish species (bighead carp, common carp, crucian carp, yellow catfish, and tilapia) for A. woodiana under laboratory conditions. No significant difference was found in the number of glochidia attached to the five fish species; however, tilapia hosted more transformed juveniles than bighead carp, common carp, or yellow catfish (p

Finite-Time Extended State Observe Based Fault Tolerant Control for Autonomous Underwater Vehicle with Unknown Thruster Fault - Xiaofeng Liu; Mingjun Zhang; Xing Liu; Wende Zhao (Journal of Marine Science and Engineering, 2022)
This paper investigates the problem of fault tolerant control (FTC) for autonomous underwater vehicles (AUVs) with multiple thrusters in the presence of current disturbances, thruster faults, and modelling uncertainty. This paper focuses on the problems of reducing the energy consumption caused by the chattering of control signals and improving the tracking accuracy of an AUV operating in deep-sea environments. In view of the problem of large energy consumption in some other methods, a fault tolerant control method for multiple-thruster AUVs based on a finite-time extended state observer (FTESO) is proposed. More specifically, a FTESO based on an integral sliding mode surface is designed to estimate the generalized uncertainty compounded using current disturbances, thruster faults, and modelling uncertainty. The fast finite-time uniformly ultimately bounded stability of the proposed FTESO is analyzed. Then, based on the estimated value of FTESO, an FTC method based on non-singular fast terminal sliding mode surfaces is developed for AUVs. The finite-time convergence of the closed-loop control system is proved theoretically. In this design, two different sliding mode surfaces are used to design FTESO and FTC, in order to avoid the appearance of singularities. Moreover, a parameter adjustment method is designed to improve tracking accuracy. Finally, comparative numerical simulations show that the proposed control scheme is effective at reducing energy consumption and improving tracking accuracy.

Autopolyploidy enhances agronomic traits and active ingredients in ‘Huaibai’, a top-grade medicinal chrysanthemum - Liwei Jiang; Xiaomeng Wang; Zhixian Geng; Yunpeng Wang; Luying Liu; Tianle Wang; Juanjuan Yu; Mingjun Li; Xiting Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Outdoor air pollution enhanced the association between indoor air pollution exposure and hypertension in rural areas of eastern China - Guoao Li; Huanhuan Lu; Wenlei Hu; Jianjun Liu; Mingjun Hu; Jialiu He; Fen Huang (Environmental Science and Pollution Research, 2022)

Ameliorating Inflammation in Insulin-resistant Rat Adipose Tissue with Abdominal Massage Regulates SIRT1/NF-κB Signaling - Tianjiao Gao; Shaotao Chen; Yiran Han; Dongmei Zhang; Yi Tan; Yutao He; Mingjun Liu (Cell Biochemistry and Biophysics, 2022)
It was the aim of this study to determine whether abdominal massage reverses high-fat diet-induced insulin resistance compared with RSV treatment. A total of sixty male Sprague-Dawley rats were randomly placed in one of four groups:the non-fat diet (NFD), the high-fat diet (HFD), the HFD with abdominal massage (HFD+ AM), and the HFD plus resveratrol (HFD+ RSV). For eight weeks, rats were fed high-fat diets to create insulin resistance, followed by six weeks of either AM or RSV. Molecular mechanisms of adipogenesis and cytokine production in rats with high-fat diets were investigated. The model rat adipose tissue showed significant improvements in obesity, glucose intolerance, and the accumulation of lipid in the body [the total cholesterol level (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C)], metabolic effects of glucose [The fasting blood glucose (FBG), Fasting insulin levels (FINS)], inflammatory status [interleukin-6 (IL-6) and tumor necrosis factor (TNF)-α, C-reactive protein (CRP)], and macrophage polarization after AM or RSV treatment. Further, AM increased SIRT1/NF-κB signaling in rat adipose tissue. Accordingly, in rat adipose tissue, our results indicate that AM regulates the secretion of proinflammatory cytokines, blood sugar levels, and related signaling pathways, contributing to improvement of IR, which may serves as a new therapeutic approach for the treatment for IR.

Abdominal Massage Alleviates Skeletal Muscle Insulin Resistance by Regulating the AMPK/SIRT1/PGC-1α Signaling Pathway - Yiran Han; Zeyuan Lu; Shaotao Chen; Chongwen Zhong; Minghui Yan; Heran Wang; Meng Meng; Mingjun Liu (Cell Biochemistry and Biophysics, 2021)
Abdominal massage (AM), a traditional Chinese medicine-based treatment method, has received considerable attention in the recent years. The aim of the present study was to investigate the effect of AM on high-fat diet (HFD)-induced insulin resistance (IR) in comparison with resveratrol (RSV) treatment. Forty-eight male Sprague-Dawley rats were randomly divided into the following four groups: standard chow diet (control group), high-fat diet (model group), HFD + abdominal massage (AM group), and HFD + resveratrol (RSV group). A rat model of IR was established by feeding HFD to rats for 8 weeks followed by treatment with AM or RSV for 4 weeks. The underlying HFD-induced IR molecular mechanisms were studied in rat serum and skeletal muscles. RSV and AM significantly improved glucose intolerance, hyperglycemia, obesity, and significantly reduced lipid accumulation [triglyceride (TC), total cholesterol (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)], adipocytokine [free fatty acids (FFA), adiponectin (ADPN)] and serum pro-inflammatory cytokines (IL-6 and TNF-α) secretion. In addition, AM activated the AMPK/SIRT1 signaling pathway in rat skeletal muscle. In conclusion, our results showed that AM could improve IR by regulating the secretion of adipocytokines, pro-inflammatory cytokines as well as related signaling pathways in the skeletal muscle of rats, which might provide insights into development of new treatment methods for the clinical treatment of IR.

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Genetic variation and differentiation of Quercus variabilis populations at phosphate and non-phosphate rock sites in southwestern China - Huawei Ji; Baoming Du; Hongmei Du; Ningxiao Sun; Xu Yang; Mingjun Peng; Hongzhang Kang; Shan Yin; Chunjiang Liu (Plant Systematics and Evolution, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Occurrence, seasonal variation and environmental impact of phosphorus flame retardants in a large scale wastewater treatment plant - Zhineng Liu; Mingjun Deng; Qihang Wu; Dave T. F. Kuo; Lixi Zeng; Zhu Wang; Ying Zhang; Xinyu Liu; Shengyu Liu; Junyan Liang; Xiaodong Hu; Bixian Mai (Environmental Science and Pollution Research, 2019)

Recent Progress in Dual-Polarization Radar Research and Applications in China - Kun Zhao; Hao Huang; Mingjun Wang; Wen-Chau Lee; Gang Chen; Long Wen; Jing Wen; Guifu Zhang; Ming Xue; Zhengwei Yang; Liping Liu; Chong Wu; et al. (Advances in Atmospheric Sciences, 2019)

Regional differences in shifts of temperature trends across China between 1980 and 2017 - Lanhui Li; Yili Zhang; Qionghuan Liu; Mingjun Ding; Partho Protim Mondal (International Journal of Climatology, 2019)
As the climate system is known to be warming unevenly, the open question of whether there has been a significant warming “hiatus” at global or regional scales has attracted worldwide attention. With annual mean air temperature ( T mean ) setting new records subsequent to 2012, it is reasonable to reanalyse the presence of an apparent decelerated warming trend in China. We therefore examined the shifts of temperature trends in China between 1980 and 2017 using homogenized records from 798 meteorological stations via the Breaks For Additive Season and Trend (BFAST) method and Mann–Kendall and Sen's slope estimator statistical tests. The results show that T mean at the country level exhibited monotonic increase with a positive break occurring around 1997, and the warming rate during 1980–2017 (0.36 °C/decade) was slightly higher than that during 1980–1997, which suggests that this positive break did not overwhelm the overall continuous warming trend. Spatial records show that most areas west of 108°E or south of 30°N within the country experienced a continual warming trend over the study period and that negative break that occurred around 2010 was major contributor to temporary decelerated warming trend detected in other areas, especially in Northeast China. Hence, this study highlights annual air temperature has continued to rise overall in China since 1980, while considerable regional differences have been detected within the shifts of temperature trends.

Assessing pollution and risk of polycyclic aromatic hydrocarbons in sewage sludge from wastewater treatment plants in China’s top coal-producing region - Qihang Wu; Zhineng Liu; Junyan Liang; Dave T. F. Kuo; Shejun Chen; Xiaodong Hu; Mingjun Deng; Haozhi Zhang; YueHan Lu (Environmental Monitoring and Assessment, 2019)

Over-Expressed FEZF1 Predicts a Poor Prognosis in Glioma and Promotes Glioma Cell Malignant Biological Properties by Regulating Akt-ERK Pathway - Mingjun Yu; Shijia Yu; Yixue Xue; Hai Yu; Duo Chen; Xiangtai Wei; Yunhui Liu (Journal of Molecular Neuroscience, 2018)

Multivariate Analysis of Water Quality of the Chenqi Basin, Inner Mongolia, China - Honglei Liu; Qiang Wu; Mingjun Wang; Meng Zhang (Mine Water and the Environment, 2018)

Displacement and Dissolution Characteristics of CO $$_{2}$$ 2 /Brine System in Unconsolidated Porous Media - Lanlan Jiang; Minghao Yu; Ying Teng; Mingjun Yang; Yu Liu; Weizhong Li; Yongchen Song (Transport in Porous Media, 2018)

Estimates of linkage disequilibrium and effective population sizes in Chinese Merino (Xinjiang type) sheep by genome-wide SNPs - Shudong Liu; Sangang He; Lei Chen; Wenrong Li; Jiang Di; Mingjun Liu (Genes & Genomics, 2017)

Assessment of diurnal variation of summer precipitation over the Qilian Mountains based on an hourly merged dataset from 2008 to 2014 - Xuemei Liu; Mingjun Zhang; Shengjie Wang; Jie Wang; Peipei Zhao; Panpan Zhou (Journal of Geographical Sciences, 2017)

Stable water isotopes of precipitation in China simulated by SWING2 models - Yanjun Che; Mingjun Zhang; Shengjie Wang; Jie Wang; Yangmin Liu; Fuxian Zhang (Arabian Journal of Geosciences, 2016)

Estimation of areal precipitation in the Qilian Mountains based on a gridded dataset since 1961 - Fang Qiang; Mingjun Zhang; Shengjie Wang; Yangmin Liu; Zhengguo Ren; Xiaofan Zhu (Journal of Geographical Sciences, 2016)

Assessment of effectiveness of nature reserves on the Tibetan Plateau based on net primary production and the large sample comparison method - Yili Zhang; Zhongjun Hu; Wei Qi; Xue Wu; Wanqi Bai; Lanhui Li; Mingjun Ding; Linshan Liu; Zhaofeng Wang; Du Zheng (Journal of Geographical Sciences, 2016)

Comparison of GCM-simulated isotopic compositions of precipitation in arid central Asia - Shengjie Wang; Mingjun Zhang; Fenli Chen; Yanjun Che; Mingxia Du; Yangmin Liu (Journal of Geographical Sciences, 2015)

A multiplex RT-PCR for simultaneous detection and identification of five viruses and two viroids infecting chrysanthemum - Xiting Zhao; Xingliang Liu; Beibei Ge; Mingjun Li; Bo Hong (Archives of Virology, 2015)

Start of vegetation growing season on the Tibetan Plateau inferred from multiple methods based on GIMMS and SPOT NDVI data - Mingjun Ding; Lanhui Li; Yili Zhang; Xiaomin Sun; Linshan Liu; Jungang Gao; Zhaofeng Wang; Yingnian Li (Journal of Geographical Sciences, 2015)

Overexpression of NPC1L1 in the livers of transgenic Bama miniature pigs accelerates lipid peroxidation - Chongli Xu; Yu Liu; Yuchen Gong; Xinping Duan; Xiaochun Tang; Mingjun Zhang; Daxin Pang; Liqing Yu; Hong Wei; Hongsheng Ouyang (Genes & Genomics, 2015)

Spatial and temporal variability in the net primary production of alpine grassland on the Tibetan Plateau since 1982 - Yili Zhang; Wei Qi; Caiping Zhou; Mingjun Ding; Linshan Liu; Jungang Gao; Wanqi Bai; Zhaofeng Wang; Du Zheng (Journal of Geographical Sciences, 2014)

Knockdown of endogenous myostatin promotes sheep myoblast proliferation - Chenxi Liu; Wenrong Li; Xuemei Zhang; Ning Zhang; Sangang He; Juncheng Huang; Yubin Ge; Mingjun Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Supplementary studies on Myxobolus tsangwuensis Chen, 1954 (Myxozoa: Myxosporea) infecting the gills of common carp Cyprinus carpio (L.): molecular and histological data - Mingjun Huang; Yang Liu; Luo Jia; Yanhua Zhai; Qiong Deng; Zemao Gu (Acta Parasitologica, 2014)
Myxobolus tsangwuensis Chen, 1954 is a common parasite infecting the gills of common carp Cyprinus carpio (L.). It was described simply in the original description and its molecular data was absent, which makes the accurate diagnosis challenging. Here we supplemented its description based on the morphological, histological and molecular data. It was characterized by the presence of small round or ellipsoidal plasmodia in the gills of host and histology showed the plasmodia developed in the capillary network of the gill lamella. Mature spores of M. tsangwuensis were ellipsodal in frontal view and lemon shaped in lateral view, averaging 11.2 ± 0.7 (10.2–12.5) μm × 9.3 ± 0.3 (8.5–10.0) μm × 6.2 ± 0.4 (5.5–7.0) μm. Spores valves were symmetrical and smooth. Occasionally, a small intercapsular appendix was observed. Two polar capsules were pyriform with different sizes, measuring 5.0 ± 0.2 (4.4–5.3) μm × 3.1 ± 0.1 (2.9–3.5) μm and 3.9 ± 0.2 (3.4–4.3) μm × 2.5 ± 0.2 (2.0–2.8) μm, respectively. Polar filaments coiled five to seven turns in large polar capsule and three to four turns in the small polar capsule. Some spores were surrounded by the mucous envelope that was not recorded in the original description. Molecular analysis revealed that the present SSU rDNA sequences did not match any available sequences in GenBank and phylogenetic analysis showed M. tsangwuensis was sister to M. basilamellaris and M. musseliusae.

In-situ observation for formation and dissociation of carbon dioxide hydrate in porous media by magnetic resonance imaging - ChuanXiao Cheng; JiaFei Zhao; YongChen Song; ZiHao Zhu; WeiGuo Liu; Yi Zhang; MingJun Yang; XiChong Yu (Science China Earth Sciences, 2013)

Extreme drought changes in Southwest China from 1960 to 2009 - Mingjun Zhang; Jinyun He; Baolong Wang; Shengjie Wang; Shanshan Li; Wenli Liu; Xuening Ma (Journal of Geographical Sciences, 2013)

Decreasing potential evapotranspiration in the Huanghe River Watershed in climate warming during 1960–2010 - Xuening Ma; Mingjun Zhang; Yaju Li; Shengjie Wang; Qian Ma; Wenli Liu (Journal of Geographical Sciences, 2012)

Design and Evaluation of a Novel Evodiamine-Phospholipid Complex for Improved Oral Bioavailability - Qunyou Tan; Shan Liu; Xueliang Chen; Mingjun Wu; Hong Wang; Huafeng Yin; Dan He; Huarong Xiong; Jingqing Zhang (AAPS PharmSciTech, 2012)

SNIP1: a new activator of HSE signaling pathway - Qiang Li; Jian An; Xianghua Liu; Mingjun Zhang; Yichen Ling; Chenji Wang; Jing Zhao; Long Yu (Molecular and Cellular Biochemistry, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Production of recombinant human lysozyme in the milk of transgenic pigs - Jia Tong; HengXi Wei; XiaoFang Liu; WenPing Hu; MingJun Bi; YuanYuan Wang; QiuYan Li; Ning Li (Transgenic Research, 2011)

Characterization of a novel human CDK5 splicing variant that inhibits Wnt/β-catenin signaling - Qiang Li; Xianghua Liu; Mingjun Zhang; Guangming Ye; Qian Qiao; Yichen Ling; Yanhua Wu; Yuanyuan Zhang; Long Yu (Molecular Biology Reports, 2010)

Functional characterization of the promoter region of human TNFAIP1 gene - Mingjun Liu; Zhenhua Sun; Aidong Zhou; Hong Li; Liping Yang; Chang Zhou; Rushi Liu; Xiang Hu; Jianlin Zhou; Shuanglin Xiang; Jian Zhang (Molecular Biology Reports, 2010)

The relationship between NDVI and precipitation on the Tibetan Plateau - Mingjun Ding; Yili Zhang; Linshan Liu; Wei Zhang; Zhaofeng Wang; Wanqi Bai (Journal of Geographical Sciences, 2007)

Vegetation change in the Mt. Qomolangma Nature Reserve from 1981 to 2001 - Wei Zhang; Yili Zhang; Zhaofeng Wang; Mingjun Ding; Xuchao Yang; Xuedong Lin; Linshan Liu (Journal of Geographical Sciences, 2007)

Land cover change along the Qinghai-Tibet Highway and Railway from 1981 to 2001 - Mingjun Ding; Yili Zhang; Zhenxi Shen; Linshan Liu; Wei Zhang; Zhaofeng Wang; Wanqi Bai; Du Zheng (Journal of Geographical Sciences, 2006)

Characteristics of grassland degradation and driving forces in the source region of the Yellow River from 1985 to 2000 - Linshan Liu; Yili Zhang; Wanqi Bai; Jianzhong Yan; Mingjun Ding; Zhenxi Shen; Shuangcheng Li; Du Zheng (Journal of Geographical Sciences, 2006)